A Chilean pattern of CSR? An Institutional Analysis of Corporate Social Responsibility in Chile - Soos, Eszter D (2017)
Today there is increasing pressure for international businesses to take into account their impact on societies in the countries where they operate and adopt CSR initiatives. However, several authors argue that international firms would not simply impose the same CSR initiatives across different national contexts, but that they would adapt to different nation-level institutions. Matten and Moon (2008) in their influential research initially proposed that differences in CSR would emerge based on institutional and national settings, while Ioannou and Serafeim (2012) suggested that there are institutional drivers shaped by different building blocks within a national business system, which would affect CSR patterns in firms.